PENGARUH EXPERIENTAL MARKETING DAN PHYSICAL ENVIRONMENT TERHADAP LOYALITAS PELANGGAN DENGAN CUSTOMER ENGANGEMENT SEBAGAI VARIABEL MEDIASI PADA TOMORO COFFEE JEPARA - April Della Lestari; Nurul Komaryatin (Universitas Dharmawangsa, 2026)
This study aims to examine how Experiential Marketing and Physical Environment influence Customer Loyalty, with Customer Engagement acting as a mediating variable at Tomoro Coffee Jepara. The increasingly competitive coffee business requires companies not only to focus on product excellence but also on the experience provided to customers. Experiential Marketing plays an important role in developing sensory, emotional, cognitive, and social experiences, while the Physical Environment includes interior design, lighting, and café ambiance, all of which shape customer perceptions. This study employs a quantitative method with a survey approach. The sample consists of 130 respondents who are customers of Tomoro Coffee Jepara, selected using purposive sampling technique. Data analysis was conducted using Structural Equation Modeling (SEM) with the assistance of SmartPLS 4.0. The findings indicate that Experiential Marketing has a significant positive effect on Customer Engagement, while the Physical Environment has a substantial but negative effect on Customer Engagement. Furthermore, Customer Engagement has a significant negative effect on Customer Loyalty. Meanwhile, the direct effect of Physical Environment on Customer Loyalty is found to be insignificant. Mediation testing reveals that Customer Engagement significantly mediates the relationship between Experiential Marketing and Physical Environment on Customer Loyalty. The R-Square value of 0.699 indicates that the model explains 69.9% of the variance in Customer Loyalty.